Standards for head injury management in acute hospitals: evidence from the six million population of the Eastern region. Issue 2 (26th January 2006) - Seeley, H M; Maimaris, C; Hutchinson, P J; Carroll, G; White, B; Kirker, S; Tasker, R C; Steward, C; Haynes, K; Hardy, D; Pickard, J D
Abstract : Objectives: To develop standards of care for head injury and thereby identify and prioritise areas of the service needing development; to report the findings from a survey of compliance with such standards in the Eastern region of UK. Methods: The standards were collaboratively developed through an inclusive and iterative process of regional surveys, multidisciplinary conferences, and working groups, following a method similar to that used by the Society of British Neurological Surgeons. The standards cover seven topics relating to all aspects of service delivery, with standards within each objective. Each standard has been designated a priority level (A, B, or C). The standards were piloted using a self-assessment questionnaire, completed by all 20 hospitals of the Eastern region. Results: Full compliance was 36% and a further 30% of standards were partially met across the region, with some areas of service delivery better than others. Seventy eight per cent of level A standards were either fully or partially met. Results were better in the north of the region compared with the south. Conclusion: A survey of compliance with the head injury standards indicate that, with their whole systems approach and subject to further refinement, they are a useful method for identifying deficiencies in service provision and monitoring for quality of care both within organisations and regionally.